Wallet Digital Cross-Generation in the Acceleration of Digital Economic Transformation - Laksamana, Rio (ITB AAS INDONESIA Surakarta, 2024)
The phenomenon of digital wallets as electronic payment transaction tools is primarily due to changes in people's lifestyles, leveraging technological advancements, and various advantages, which consequently influence the decision to use digital wallets compared to other options. These digital wallet products are regulated through the regulations and rules established in Bank Indonesia Regulation No. 18/40/PBI/2016 and Bank Indonesia Circular Letter No. 18/41/DKSP regarding Payment Transaction Processing Implementation. Indonesia is ranked as the fourth most populous country with a population of 277.7 million people, and it is also one of the world's largest populations of internet users, totaling 204.7 million internet users in the country as of January 2022, or 73.7% of the entire Indonesian population. The aim of this research is to identify the differences in digital wallet usage frequency based on demographic factors, users' perceptions of digital wallets, and respondents' views on their interest in digital wallets in the future. The research method employs a direct field survey with a quantitative descriptive approach. The results indicate that the frequency of digital wallet usage is still low and uneven, while users' perceptions and interest in digital wallets are high. The findings of this research corroborate the findings of previous studies.